PACHAMAMA HAMPIA QHORANCHISKUNA (THE MEDICINAL PLANTS OF OUR MOTHER LAND). EXPERIENCES IN ECOLOGICAL CULTIVATION OF MEDICINAL AND AROMATIC ANDINE PLANTS AT THE SACRED VALLEY OF THE INCAS (Revista de Ciências Agroveterinárias, 2006)
In this paper, where the original title is in the Quechua idiom, we present the experience on the sustainable handling of medicinal and aromatic plants in countryside communities of the Peruvian andine south. The organic cultivation, the implantation of appropriate technologies for the medicinal plants’ transformation, and the commercialization in the solidary market, generated an elevation in the self-esteem of the countryside families and has contributed in the cultural reaffirmation of the andine communities with respect to the andine traditional medicine knowledge. All of it conducts to more respect of mother earth (pachamama in the Quechua idiom), which “creates” and offers us a valuable preventive and curative biodiversity in order to reach a healthy life.
Keywords: medicinal plants; organic cultivation; Andine traditional medicine.